Regional Anesthesia Conversion to General Anesthesia during Cesarean Section of a Woman with Antepartum Hemorrhage due to Placenta Previa and Ovarian Cyst with Moderate Confirmed COVID-19: A - Supraptomo, Raden Theodorus; Sunjoyo, Ageng (Open Access Macedonian Journal of Medical Sciences, 2022)
Physiological changes during pregnancy and COVID-19 may affect one another. This report presents a 37-year-old female G4P10021 with gestational age 37+2 weeks infected with COVID-19 in Dr. Moewardi Hospital Surakarta, Central Java, Indonesia. The patient was diagnosed with antepartum hemorrhage due to total placenta previa with low-risk Morbidly Adherent Placenta score, a history of cesarean section, and ovarian cyst. The patient underwent conversion from spinal anesthesia to general anesthesia. Within 40 min after spinal anesthesia, the patient complained shortness of breath, which then worsened into decreased consciousness and inadequate spontaneous breathing. This may be complicated by the COVID-19 infection which has several effects on pregnancy.